Work Load Analysis dengan Full Time Equivalent Sebagai Pertimbangan Pembagian Beban Kerja Karyawan - M. Nur Muchlisin (Psyche 165 Journal, 2021)
PT TTA is a coal concession company that is part of the AIS Group. The HCGS Department as the manager responsible for managing human resources at PT TTA is one of the factors that can improve organizational performance. Management and planning of human resources can be done with workload analysis. Workload analysis is a method used to determine the amount or quantity of labor required. Full time equivalent is a workload calculation method by comparing the time used to complete various jobs and the available effective working time. Based on the results of these measurements, workload analysis was carried out on 6 HCGS employees, 3 of whom were overloaded, one employee was overloaded, and 2 employees had normal workloads. An even distribution of workload to employees is expected to improve organizational performance and reduce employee work stress